Leaching of lead metallurgical slag in citric solutions--implications for disposal and weathering in soil environments - Ettler, Vojtech; Komárková, Marie; Jehlicka, Jan; Coufal, Pavel; Hradil, David; Machovic, Vladimír; Delorme, Fabian (Chemosphere, 2004)
Metallurgical slags from primary lead smelting were submitted to a 30-day batch leaching procedure in 20 and 8 mM citric solutions in order to determine the kinetics of release of Pb, Cu, Zn and As. The experiment was coupled with the PHREEQC-2 speciation-solubility modelling and mineralogical study of newly formed products (SEM/EDS, XRD, TEM/EDS and Raman spectrometry). A strong scavenging of metals and metalloids from the 8 mM citric leachate was observed due to the formation of newly formed products. The secondary precipitate consisted of well-developed calcite (CaCO3) crystals and amorphous organo-mineral matrix composed of hydrous ferric oxides and amorphous SiO2. Metals (Pb, Zn, Cu) and arsenic released into the solution were subsequently bound onto the newly formed product (adsorption on oxides) or trapped within the calcite structure (Zn, Mn). Similar scavenging mechanism can be taken into account in real soil systems with lower concentration of citric acid. Then, the covering of slag dumps with a thick soil layer and subsequent re-vegetation might be a possible scenario for slag management on some metallurgical sites.
Keywords: olovo; chemické modely; Soil Pollutants; látky znečišťující půdu; termodynamika; kyselina citronová; Lead; Waste Products; spektrální analýza; Kinetics; Thermodynamics; Models, Chemical; Citric Acid; Hydrogen-Ion Concentration; odpadky - odstraňování; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Spectrum Analysis; Metallurgy; odpadní produkty; koncentrace vodíkových iontů; Refuse Disposal; hutnictví; kinetika